Analyzing English Reading Skills Through Project Based Learning Approach in EFL Classroom - Haslinda; Andi Sadapotto; Syamsu Tang; Sam Hermansyah (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study aims to analyze the effectiveness of the Project-Based Learning (PBL) approach in improving reading comprehension skills among students of English as a Foreign Language (EFL). The research focused on fourth-semester students of the English Education Study Program at the University of Muhammadiyah Sidenreng Rappang who had engaged in reading instruction using the PBL approach. A descriptive qualitative method was employed, with data collected through questionnaires, semi-structured interviews, and documentation. The findings revealed that PBL enhances students’ active engagement, motivates them to read, and supports the development of reading strategies such as skimming, scanning, making inferences, and identifying main ideas. The most effective aspects of PBL included group work, discussions, and project presentations, all of which significantly contributed to improving academic reading comprehension. However, the study also identified challenges such as unequal task distribution, limited time, and ineffective group coordination. The results suggest the need for more intensive lecturer guidance, training in critical reading strategies, and the integration of technology into PBL implementation. Overall, PBL is considered a relevant and effective approach for enhancing reading skills in EFL contexts